PENGARUH PERSEPSI HARGA DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI BARBERSHOP ‘X’ KOTA PADANG - Abdilla, Mohammad; Husni, Erdasti (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2018)
This study aims to determine the effect of price perception and service quality partially and simultaneously in Barbershop 'X' Padang city in 2017. The sample of 138 people with purposive sampling technique using Chocran formula. Research data is quantitative scale Likert score 1 - 5 collected by questionnaire. Analysis of data using multiple linear regression using SPSS for windows version 19 program. Before the data processed first tested the validity and reliability test. All indicators of price perceptions, service quality and purchasing decisions are valid because r count > r table = 0.197 and reliable because all values of Cronbach's Alpha > alpha = 0.60. Likewise all the classical assumptions of normality, multicolinearity and heteroscedasticity are met so that research data worthy of use. Multiple linear regression equation Y = 5.276 + 0.427X1 + 0.504X2 + e where service quality is more dominant influence purchasing decision than price perception. The relation of price perceptions, service quality with purchasing decision r = 0.632 (strong) and adjusted R square 0.517 where purchasing decision is explained by price perception and service quality 51.7% and the rest 48.3% influenced by other factors not included in research model. The research hypothesis is partially accepted at 5% significance level because p value 0.026 < 0.05 and p value 0.033 < 0.05 also simultaneously because F arithmetic > F table (43.627 > 3.257Keywords : price perception, service quality and purchase decision